(untitled) (La U Investiga, 2018)
To establish the association between the occurrence of coronary event and the lipid profile in elderly patients (over 70 years old) with typical risk factors. A comparative study was carried out, where 40 patients were assigned to the case group with coronary disease (AMI-Angina) and 80 patients to the control group without coronary disease, both groups without statistically significant differences with respect to different variables (age, gender, comorbidities). or smoking), attended at the Endocrinology Service of the Specialties Hospital of the Armed Forces Nº1 Quito-Ecuador. The association between coronary event and high values of low density lipoproteins was statistically significant (OR: 4, CI: 1.31-12.74, p <0.05), being higher in the group of 70 to 79 years (OR : 3.8) than in the 80 to 89 years (OR: 2.5). 62.5% of the patients in the case group who received lipidlowering treatment did not meet the low-density lipoprotein targets. However, there was no statistically significant difference between strict adherence to low density lipoprotein targets and the presence of coronary event (OR: 0.7 CI: 0.35-1.6), in patients over 80 years of age, although no statistically significant association was found in the levels of very low density lipoprotein, the triglyceride /HDL index and cardiovascular risk, as well as there was no association between compliance with low density lipoprotein targets and presence of coronary event ( OR: 0.7 CI: 0.35-1.6), in patients older than 80 years.